Great pianists and pedagogues: In conversation with Carola Grindea - Grindea, Carola (London Kahn & Averill Publishers, 2007)
More than 40 interviews with some of the greatest pianists and piano teachers of the 20th century are assembled in this unique collection. The contributors provide fascinating comments about their experiences, their first encounters with the piano, and their lives as performers and teachers. Filled with the musical ideas and traditions of professional piano players, this distinctive work provides a notable insight into the world of music.